2021
DOI: 10.1021/jacs.1c01088
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Molecular Geometry and Solution Self-Assembly of Amphiphilic Polypeptoid Block Copolymers by Side Chain Branching Pattern

Abstract: Solution self-assembly of coil-crystalline diblock copolypeptoids has attracted increasing attention due to its capability to form hierarchical nanostructures with tailorable morphologies and functionalities. While the N-substituent (or side chain) structures are known to affect the crystallization of polypeptoids, their roles in dictating the hierarchical solution self-assembly of diblock copolypeptoids are not fully understood. Herein, we designed and synthesized two types of diblock copolypeptoids, i.e., po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(104 citation statements)
references
References 70 publications
(193 reference statements)
3
101
0
Order By: Relevance
“…In addition, they also have shown that well-defined block copolypeptoids, e.g., poly(N-methyl glycine)- b -poly(N-butyl glycine) (PNMG- b -PNBG), can be produced by controlled ROP with sequential monomer addition [ 61 , 62 ]. In our previous studies [ 60 , 70 , 79 , 84 ], a variety of well-defined amphiphilic diblock copolypeptoids that comprised of at least one crystallizable block with relatively low PDIs have been synthesized via benzyl amine-initiated ROPs of R-NCAs in a sequential manner, allowing us to further investigate their CDSA behaviors in solution. There are several aliphatic N-substituents can be readily used for the molecular design ( Figure 1 ).…”
Section: Polypeptoids Bearing Alkyl Side Chains: Synthetic Methods and Their Phase Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, they also have shown that well-defined block copolypeptoids, e.g., poly(N-methyl glycine)- b -poly(N-butyl glycine) (PNMG- b -PNBG), can be produced by controlled ROP with sequential monomer addition [ 61 , 62 ]. In our previous studies [ 60 , 70 , 79 , 84 ], a variety of well-defined amphiphilic diblock copolypeptoids that comprised of at least one crystallizable block with relatively low PDIs have been synthesized via benzyl amine-initiated ROPs of R-NCAs in a sequential manner, allowing us to further investigate their CDSA behaviors in solution. There are several aliphatic N-substituents can be readily used for the molecular design ( Figure 1 ).…”
Section: Polypeptoids Bearing Alkyl Side Chains: Synthetic Methods and Their Phase Behaviormentioning
confidence: 99%
“…For example, in the case of racemic 2-ethyl-l-hexyl side chains, it was found that relatively short poly (N-2-ethyl-1-hexyl glycine) (PNEHG) molecules with DP n ≀ 20 are amorphous with no first-order transition observed by DSC [ 90 , 91 ]. On the other hand, longer PNEHG chains, e.g., DP n ≄ 100, exhibit a single first-order thermal transition with a small enthalpic change, but are still in sharp contrast with poly (N-octyl glycine) (PNOG) homopolymer which also possesses eight carbon atoms on their side chains [ 84 , 97 ]. Our recent WAXD measurements on PNOG and PNEHG homopolymers with similar DP n (DP n ≈ 100) revealed the effect of side chain branching on the molecular geometry and supramolecular assembly [ 84 ].…”
Section: Polypeptoids Bearing Alkyl Side Chains: Synthetic Methods and Their Phase Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Next to BCPs with a PFS block, a variety of other crystallizable polymer blocks were employed in CDSA, e.g. polyethylene (PE) [ 68 , 92 , 93 , 94 ], poly(ethylene oxide) [ 95 ], polyesters (poly( Δ -caprolactone) (PCL) or poly( L -lactide) (PLLA)) [ 86 , 96 , 97 , 98 , 99 , 100 , 101 ], polycarbonate [ 102 ], poly(2- iso -propyl-2-oxazoline) (P i PrOx) [ 103 , 104 ], liquid crystalline polymers [ 71 , 105 ], poly(vinylidene fluoride) [ 106 ], polypeptoids [ 107 , 108 ], and various conjugated polymers (e.g., poly(3-hexyl thiophene) (P3HT) and OPV) [ 75 , 109 , 110 , 111 , 112 , 113 ].…”
Section: Crystallization-driven Self-assembly (Cdsa)mentioning
confidence: 99%
“…This work provides an understanding of the relationship between peptoid sequences, assembly nanostructures, and its crystallization pathways. A recent work [ 35 ] compares the crystalline packing and hierarchical assembly pathways of PNMG‐ b ‐PNDG and a similar PNMG‐ b ‐PNEHG (poly‐( N ‐methylglycine)‐ b ‐poly( N ‐2‐ethyl‐1‐hexylglycine)) in Figure 4B. With linear N‐alkyl substituents, PNDG blocks pack into lamellar‐like crystalline structures which drives PNMG‐ b ‐PNDG assemble into a hierarchical microflower‐like particles.…”
Section: Diblock Linear Copolypeptoidsmentioning
confidence: 99%